Dinamika Aliran Keagamaan Sempalan: Tinjauan Persepektif Sosiologi Agama - Abbas Langaji (Hikmah: Journal of Islamic Studies, 2016)
Abstract Currently, the efforts are focused on explaining fragment religious flows from social science approaches. The social sciences approaches are not only explain how a fragment religious flow appeared and developed but also can explain how to overcome religious conflict in the communities. In this case, The Religion colleges have important roles. In relation to the increasing of educational level of community, which is influenced by the role of religion colleges. The religion colleges support the civil society approach with universal values which existed in all religions such as democracy, tolerance, egalitarianism spirits, that is why the app roaches with social science basics are important to be intensified in understanding and responding towards the fragment religious flows phenomenon. This paper explains about the fragment religious flows from the sociological perspectives and initiates the strategic roles of religion colleges in solving the problem of developed religious conflicts. Keywords: Religious flows, Fragment, Sociologi of religion Abstrak Dewasa ini mulai dikedepankan upaya menjelaskan realitas aliran keagamaan sempalan dengan pendekatan ilmu-ilmu sosial. Pendekatan ilmu-ilmu sosial ini bukan hanya untuk menjelaskan bagaimana suatu aliran keagamaan sempalan muncul dan berkembang, tetapi dalam ranah praktis cukup efektif dalam meredam gejolak yang terjadi di masyarakat, bahkan dalam penyelesaian konflik keagamaan yang terjadi. Dalam konteks ini peran Perguruan Tinggi Agama menjadi penting. Perguruan Tinggi Agama, yang mendorong pendekatan civil society dengan mengedepankan nilai-nilai universal yang terdapat pada semua ajaran agama, seperti demokrasi, toleransi, semangat egalitarianisme, maka pendektan berbasis ilmu-ilmu sosial perlu semakin ditingkatkan. Tulisan ini menjelaskan dinamika aliran keagamaan sempalan dalam perspektif sosiologi dan menggagas peran strategis Perguruan Tinggi Agama dalam mengatasi konflik keagamaan yang berkembang. Kata Kunci: Aliran Keagamaan, Sempalan, Sosiologi Agama